(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-2-94-102 The article presents the forms of irony in the memoir discourse of A.I. Solzhenitsyn, analyzes their functions. The writer’s ironic thinking is shown at the compositional, problematic, and stylistic levels of the memoirs in the books “The Oak and the Calf” and “Between Two Millstones”. The author of the article proves that with the help of irony as a stylistic device Solzhenitsyn expresses his author’s position and his personal attitude to the events and people, but irony is not the basis of Solzhenitsyn’s thinking as a Christian writer and a realist writer. Key words: A. I. Solzhenitsyn, “The Oak and the Calf”, “Between Two Millstones”, writer’s memoirs, author in memoirs, irony